A Comparative Study of Percutaneous Nephrolithotripsy and Extracoeporeal Shockwave Lithotripsy For The Treatment of Lower Pole Kidney Stone of Size 10-20 mm - Shrestha, Naresh Man (Journal of Nepalgunj Medical College, 2021)
Introduction: A renal stone is commonly found at the Lower-pole of the kidney. Studies have reported various opinions about efficacy and safety of Percutaneous Nephrolithotripsy and Extracoeporeal Shockwave Lithotripsy for the treatment of lower pole stone of size 10-20 mm. Aims: The present study aimed to compare between Percutaneous Nephrolithotripsy and Extracoeporeal Shockwave Lithotripsy for safe and effective treatment of lower pole stone of size 10-20 mm. Methods: It is a prospective study conducted from December 2019 to November 2020 in the Urology Department of Nepalgunj Medical College. Total 66 patients under inclusion criteria were divided into two groups. Group I (32 patients) was allocated for patients who were treated under Percutaneous Nephrolithotripsy while Group II (34 patients) was allocated for patients who were treated with Extracoeporeal Shockwave Lithotripsy. Two groups were compared for stone free rate, retreatment rate, auxiliary treatment (%), operation time, hospital stay, haematuria, blood transfusion, obstruction and fever. Results: The stone free rate was significantly higher in Group I when compared to Group II. While the rate of retreatment and auxiliary treatment were significantly lower in Group I than Group II. However, mean hospital stay, mean operation time and the rate of haematuria was significantly higher in Group I when compared to group II. There were no statistically significant differences between Group I and Group II for post-operative complications such as, blood transfusion, obstruction and fever. Conclusion: Stone free rate was significantly higher in Group I while retreatment rate and auxiliary treatment rate were significantly higher in Group II. Therefore, Percutaneous Nephrolithotripsy is more effective for the treatment of the lower pole stone of size 10-20mm when compared to Extracoeporeal Shockwave Lithotripsy. However, duration of hospital stay and operation time were longer and incidence of haematuria was higher in Percutaneous Nephrolithotripsy than Extracoeporeal Shockwave Lithotripsy.